744 Single cell profiling of acute myeloid leukemia (AML) and its microenvironment reveals a CD8 continuum and adaptable T cell plasticity in response to PD-1 blockade-based therapy. (10th December 2020) - Abbas, Hussein; Hao, Dapeng; Tomczak, Katarzyna; Barrodia, Praveen; Im, Jin Seon; Reville, Patrick; Alaniz, Zoe; Wang, Wei; Wang, Ruiping; Wang, Feng; Al-Atrash, Gheath; Takahashi, Koichi; et al.
Abstract : Background: Allogeneic stem cell transplantation can cure relapsed/refractor (R/R) AML via grafted T cells versus leukemia effect, but not a viable option to many patients. By combining azacitidine with nivolumab, we harnessed T cell activity and demonstrated 33% response rates. The tumor microenvironment (TME) factors impacting response and resistance to PD-1 blockade-based treatment in AML are unknown. Methods: We performed single cell RNA sequencing (scRNAseq) on 113, 394 bone marrow (BM) cells, paired with >30, 000 single cell T cell receptor (scTCR) repertoires, from 8 pre- and 14 post- azacitidine/nivolumab treatment aspirates of 8 R/R AML patients (median age 73 years; 3 responders; 3 non-responders; 2 stable disease) (figure 1 ). Results: Inferred copy number loss of chromosome 7/7q (chr7/7q) by scRNAseq was associated with resistance to azacitidine/nivolumab (figure 2 A), which was validated in a larger cohort based on clinical karyotyping (figure 2 B). There was significant enrichment (q<0.005) for IFNg pathway in chr7/7q. We identified marked variation in the T cell components across AML patients at pre- and post- treatment, demonstrating significant dynamic changes in CD4, CD8 and non-classical T cells populations, including MAIT (figure 3 A-B). Among CD8 cells, we identified a unique GZMK-enriched population that was highest at pretreatment in responders. Pseudotemporal trajectory analysis revealed a continuum of CD8 cell states, intermediated by the less exhausted, GZMK-enriched CD8 population (figure 3 C-D). GZMK also discriminated between 2 MAIT populations. GZMK-enriched cells had increased expression of the stem-like T cell transcription factor TCF7, and the T cell memory transcription factor EOMES. GZMK expression was associated with improved survival in de novo TCGA AML cohort (p=0.0017). scTCR clonotype assessment revealed shared clonotypes with the terminally effector CD8 CTL cells following PD-1 blockade. Following treatment, novel clones represented 38.7% (39/101) of total clones, followed by contracted clones (32.6%) and expanded (28.7%) clones (figure 3 E-F). However, 76.9% and 72.4% of novel and expanded clones were contributed by the responders. Non-responders contributed only 5% and 3.4% of the novel and expanded clones, respectively. Conclusions: Chr7/7q loss is associated with resistance to PD-1 blockade. CD8 cells exist in a continuum in BMs of patients with AML and GZMK expression identifies a stem-like, memory T cell subset. The subverted T cells can be reinvigorated via PD-1 blockade and induce responses in AML driven via novel and expanded clones demonstrating AML T cell plasticity and adaptability. Further functional characterization of GZMK expressing lymphocytes in mediating antileukemic responses is underway. Ethics Approval: The study was approved by IRB at MD Anderson Cancer Center